2022
DOI: 10.5194/egusphere-2022-1171
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Climatology of the Mount Brown South ice core site in East Antarctica: implications for the interpretation of a water isotope record

Abstract: Abstract. Water stable isotope records from ice cores (δ18O and δD) are a critical tool for constraining long-term temperature variability in the high-latitudes. However, precipitation in Antarctica consists of semi-continuous small events and intermittent extreme events. In regions of high-accumulation, this can bias ice core records towards recording the synoptic climate conditions present during extreme precipitation events. In this study we utilise a combination of ice core data, re-analysis products and m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 36 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…For simplicity in this study we will hereafter refer to the 2017/2018 ice cores as 'MBS' unless comparing to the earlier drilling effort. Crockart et al (2021) and Jackson et al (2022) found the snowfall accumulation regime at MBS to follow a seasonal cycle of higher precipitation during the polar winter (March-October), and lower precipitation during December/January. Variability between accumulation records across the site was present, due to the prevailing easterlies and resulting surface features (Figure 1), which in some cases were found to be of equivalent height to the satellite era mean annual accumulation rate of 0.3 metres ice equivalent (m.i.e.)…”
Section: Mount Brown South Drilling Site Characteristicsmentioning
confidence: 98%
See 3 more Smart Citations
“…For simplicity in this study we will hereafter refer to the 2017/2018 ice cores as 'MBS' unless comparing to the earlier drilling effort. Crockart et al (2021) and Jackson et al (2022) found the snowfall accumulation regime at MBS to follow a seasonal cycle of higher precipitation during the polar winter (March-October), and lower precipitation during December/January. Variability between accumulation records across the site was present, due to the prevailing easterlies and resulting surface features (Figure 1), which in some cases were found to be of equivalent height to the satellite era mean annual accumulation rate of 0.3 metres ice equivalent (m.i.e.)…”
Section: Mount Brown South Drilling Site Characteristicsmentioning
confidence: 98%
“…Coastal East Antarctica is subject to maritime moisture intrusions which result in intense precipitation events occurring over hours to days, a subset of which reach thresholds to be classified as atmospheric rivers (Gorodetskaya et al, 2014;Turner et al, 2019;Wille et al, 2021). At MBS, intense precipitation events on average account for 44% of annual accumulation (Jackson et al, 2022). These events are strongly related to mid-latitude blocking in the southern Indian Ocean to the northeast of MBS, which channels warm and moist maritime air masses to the site (Jackson et al, 2022;Pohl et al, 2021;Udy et al, 2021Udy et al, , 2022.…”
Section: Mount Brown South Drilling Site Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…When compared to interior sites, the coastal regions experience smaller temperature anomalies during EPEs due to frequent synoptic cyclone landfall and advection of warm airmasses. The high-temperature anomalies during EPEs can cause a significant warm bias in the ice-core records (Jackson et al, 2022;Servettaz et al, 2020), and reconstruction of ice-core isotope data will overestimate reconstructed temperature, if this warm bias is not taken into account (Noone & Simmonds, 1998;Servettaz et al, 2020).…”
Section: Temperaturementioning
confidence: 99%